A strategy to enhance the insecticidal potency of Vip3Aa by introducing additional cleavage sites to increase its proteolytic activation efficiency - Kun Jiang; Zhe Chen; Yiting Shi; Yuanrong Zang; Chengbin Shang; Xi Huang; Jiahe Zang; Zhudong Bai; Xuyao Jiao; Jun Cai; Xiang Gao (Engineering Microbiology, 2023)
Microbially derived, protein-based biopesticides have become a vital element in pest management strategies. Vip3 family proteins from Bacillus thuringiensis have distinct characteristics from known insecticidal Cry toxins and show efficient insecticidal activity against several detrimental lepidopteran pests. They are considered to be a promising toxic candidate for the management of various detrimental pests. In this study, we found that in addition to the preliminary digestion sites lysine, there are multiple cleavage activation sites in the linker region between domain I (DI) and DII of Vip3Aa. We further demonstrated that by adding more cleavage sites between DI and DII of Vip3Aa, its proteolysis efficiency by midgut proteases can be significantly increased, and correspondingly enhance its insecticidal activity against Spodoptera frugiperda and Helicoverpa armigera larvae. Our study promotes the understanding of the insecticidal mechanism of Vip3 proteins and illustrates an easily implementable strategy to increase the insecticidal potency of Vip3Aa. This facilitates their potential future development and efficient application for sustainable agriculture.